Tío Vallejo, Gabriela (Comp.) La república extraordinaria. Tucumán en la primera mitad del siglo XIX. Rosario, Prohistoria, 2011, 336 p. - Ayrolo, Valentina (2011)
Fil: Ayrolo, Valentina. CONICET; Universidad Nacional de Mar del Plata.